Inheritance of freezing resistance in tuber-bearing Solanum species: evidence for independent genetic control of nonacclimated freezing tolerance and cold acclimation capacity. - Stone, J M (1993)
Frost or winter survival is regarded as a complex trait with polygenic inheritance. Two major components of this survival in crop plants are freezing tolerance in the nonacclimated state and cold acclimation capacity. To date researchers have not distinguished the two components as separate heritable traits. The mode of inheritance of these two traits was investigated in F1 and backcross populations of two wild diploid potato species (Solanum commersonii and Solanum cardiophyllum) exhibiting extremes of freezing tolerance and acclimation capacity. Precise assessment of these two traits allowed distinction of small but significant differences among genotypes. The two traits were not correlated in segregating populations, suggesting independent genetic control. Analyses of generation means indicate that all of the variance for acclimation capacity and a major proportion of the variance for the nonacclimated freezing tolerance can be best explained by an additive-dominance model with both traits being partially recessive. Recovery of parental phenotypes in limited populations suggests that both traits are controlled by relatively few genes. To our knowledge this is the first study demonstrating independent genetic control of the two main traits associated with frost or winter survival. Our results show that it should be possible to incorporate these traits from wild germ plasm into cultivated crop plants by independent selection. These results help explain the lack of progress in improving winter survival through field selection. Furthermore, our study demonstrates relative simplicity of the inheritance of cold acclimation, thus providing avenues for understanding the link between biochemical and genetic aspects of low-temperature stress in crop plants.